ANALYSIS OF CAROTENOID CONTENT OF CRUDE EXTRACT OF TONGKAT LANGIT BANANA FRUIT (Musa troglodytarum) USING NIR SPECTROSCOPY (NEAR INFRARED) - Samson, Efraim; Semangun, Haryono; Rondonuwu, Ferdy S. (Majalah Obat Tradisional, 2013)
Carotenoids found in fruits and vegetables, plays an important role in preventing human diseases, including cardiovascular disease, cancer and other chronic diseases. However, many of the methods used in the determination of the chemical composition in particular for food takes a long time and the cost is quite expensive. Currently a number of instrumentation techniques have been developed to determine chemical content quickly. One example is the technique of measurement using NIR spectroscopy. In this study, NIR spectroscopy is used for the analysis of estimation of carotenoids crude extract of long and short âtongkat langitâ bananas (Musa troglodytarum). The results obtained show that this fruit contains Î²-carotene, because the area of wave numbers 5000 to 5500cm-1 is similar between the pattern of Î²-carotene spectrum marker and the pattern of carotenoid pigment tongkat langit banana spectrum.